Organizational Resilience Amidst Uncertainty: The Strategic Role of Agile Governance - Ilmi, maulida; Maulana, Akbar (Rumah Jurnal, University of Jember, 2025)
Global uncertainty marked by pandemics, technological disruption, and economic crises demands organizations, especially the public sector, to enhance adaptive and responsive capacities. Agile governance emerges as a strategic approach emphasizing flexibility, collaboration, and policy iteration to strengthen organizational resilience. This article examines the role of agile governance in building organizational resilience amid uncertainty, integrating the latest theories and recent case studies in Indonesia. The findings reveal that informal implementation of agile governance principles has improved organizational adaptability, despite persistent structural and cultural challenges. These results offer significant contributions to the development of policies and practices for public sector governance in a dynamic era.